Factors Influencing the Demoralisation Syndrome of Post‐Operative Patients With Breast Cancer: A Cross‐Sectional Study - Yuxin Huang; Panpan Zhuang; Aixuan Guan; Xiu Rong Ren; Lichun Xu (Nursing Open)
ABSTRACT Aim We explored demoralisation syndrome among post‐operative patients with breast cancer and its relationship with patients' body image and marital intimacy. Design A cross‐sectional study. Methods In this cross‐sectional study, 237 patients with breast cancer who were hospitalised in the breast surgery department of Grade A tertiary hospital in Xiamen, China from June 2022 to December 2023 and met the standards of adaxation were selected by the convenience sampling method. The survey tool consists of four parts: general data questionnaire, demoralisation scale‐II (DS‐II), quality of relationship index (QRI) and body image scale (BIS). Results In this study, we examined the demoralisation syndrome in 237 post‐operative breast cancer patients, predominantly aged 45–59 years (47.3%), with the majority living with family (94.1%) and having children (95.4%). A small proportion (5.9%) lived alone, and 3% were uninsured, opting to pay for their treatment out‐of‐pocket. The majority (83.1%) had undergone mastectomy, and 51.9% visited the hospital for chemotherapy, with 5.1% experiencing disease recurrence. The mean demoralisation score was 8.52 (SD = 8.47). We found that 22.8% had moderate and 14.8% had severe demoralisation symptoms. Socioeconomic factors such as age, residence, income, tumour staging, post‐operative time, hospital purpose and disease recurrence were associated with demoralisation. Multivariate analysis revealed that income, cancer stage, recurrence, quality of recovery index (QRI) and BIS were independent influencing factors for demoralisation syndrome after breast cancer surgery. These findings highlight the importance of considering a range of patient characteristics when addressing demoralisation in post‐operative breast cancer patients. Patient Contribution Demoralisation syndrome in patients after breast cancer surgery is influenced by a combination of sociodemographics, disease, intimate relationship and body image. Clinical medical staff should accurately evaluate and identify patients with demoralisation syndrome after breast cancer surgery and formulate and implement personalised intervention strategies according to their physical conditions and possible influencing factors, so as to reduce the incidence of demoralisation syndrome and improve the quality of life.